Analysis of Author Productivity in Lentera Pustaka Journal: Library, Information, and Archival Studies, Diponegoro University 2016-2024 - Wirayuda, I Made Indra (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2025)
Background of the study: Bibliometric analysis can help researchers in knowing the trend of scientific works. There are several laws in bibliometric analysis such as Zipf's, Bradford's, or Lotka's laws. Lotka's law is used to analyze author productivity in journals. Lentera Pustaka Journal of Library, Information, and Archival Science Studies is a journal managed by the Faculty of Cultural Studies, Diponegoro University, which has currently published 120 articles by 101 authors. Author productivity analysis was carried out on the Lentera Pustaka journal published in 2016 to 2024 using the Lotka law. Purpose: This analysis was conducted to determine the productivity of authors during the 9 years of publication of the Lentera Pustaka journal. Methods: This analysis uses bibliometric analysis techniques with Lotka's law which focus on author productivity in the Lentera Pustaka journal. Finding: From the results of Lotka's calculations, a constant value of 0,878 was obtained, which means that the contribution of a particular author to a particular article in the Lentera Pustaka journal has a value of 87,8% of the total number of authors. From the exponent value of 3,289, an observation value of 85,15% was obtained, which is quite close to the Lotka value of 87,8%. The results of the Kolmogorov-Smirnov test show that the maximum deviation value is smaller than the critical value. Conclusion: Lotka's law in calculating author productivity in the Lentera Pustaka journal can be accepted both theoretically and in terms of observation, and means that there is good productivity from article authors. Keywords: bibliometric, Lotka’s law, author productivity, journal --------------------------------------------------------------------------------------------------------------------------------------------------------------------- Analisis Produktivitas Penulis Pada Jurnal Lentera Pustaka: Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, Universitas Diponegoro Tahun 2016-2024 ABSTRAK Latar Belakang: Analisis bibliometrik dapat membantu peneliti dalam mengetahui tren karya ilmiah. Terdapat beberapa kaidah di dalam analisis bibliometrik seperti kaidah Zipf, Bradford, ataupun Lotka. Kaidah Lotka digunakan untuk menganalisis produktivitas penulis pada jurnal. Jurnal Lentera Pustaka Kajian Ilmu Perpustakaan, Informasi, dan Kearsipan merupakan jurnal yang dikelola oleh Fakultas Ilmu Budaya Universitas Diponegoro, yang saat ini telah menerbitkan 120 artikel oleh 101 penulis. Analisis produktivitas penulis dilakukan terhadap jurnal Lentera Pustaka terbitan tahun 2016 hingga 2024 dengan menggunakan kaidah Lotka. Tujuan: Analisis ini dilakukan untuk mengetahui produktivitas penulis selama 9 tahun terbitan jurnal Lentera Pustaka. Metode: Analisis ini menggunakan teknik analisis bibliometrik dengan kaidah Lotka yang berfokus terhadap produktivitas penulis pada jurnal Lentera Pustaka. Temuan: Dari hasil perhitungan Lotka didapatkan nilai konstanta sebesar 0,878 yang mengartikan bahwa kontribusi penulis tertentu terhadap artikel tertentu pada jurnal Lentera Pustaka memiliki nilai sebesar 87,8% dari total jumlah penulis. Dari nilai eksponen sebesar 3,289, kemudian didapatkan nilai pengamatan sebesar 85,15% yang cukup mendekati nilai Lotka 87,8%. Hasil uji Kolmogorov-Smirnov menunjukkan nilai deviasi maksimum lebih kecil daripada nilai kritis. Kesimpulan: Kaidah Lotka dalam perhitungan produktivitas penulis di jurnal Lentera Pustaka dapat diterima baik secara teoritis maupun secara pengamatan, serta mengartikan bahwa terdapat produktivitas yang baik dari penulis artikel. Kata kunci: Bibliometrik, Kaidah Lotka, Produktivitas penulis, Jurnal